Trees, forests and water: Cool insights for a hot world - Ellison, David; Morris, Cindy E.; Locatelli, Bruno; Sheil, Douglas; Cohen, Jane; Murdiyarso, Daniel; Gutierrez, Victoria; Noordwijk, Meine van; Creed, Irena F.; Pokorny, Jan; Gaveau, David; Spracklen, Dominick V.; et al. (Global environmental change, 2017)
Effects of forests on water and climate at local, regional and continental scales through change in water and energy cycles. (1) Precipitation is recycled by forests and other forms of vegetation and transported across terrestrial surfaces to the other end of continents. (2) Upward fluxes of moisture, volatile organic compounds and microbes from plant surfaces (yellow dots) create precipitation triggers. (3) Forest-driven air pressure patterns may transport atmospheric moisture toward continental interiors. (4) Water fluxes cool temperatures and produce clouds that deflect additional radiation from terrestrial surfaces. (5) Fog and cloud interception by trees draws additional moisture out of the atmosphere. (6) Infiltration and groundwater recharge can be facilitated by trees. (7) All of the above processes naturally disperse water, thereby moderating floods. [Display omitted] •We review the advantages of forests highlighted in the literature on forest, water and energy cycle interactions.•Forest, water and energy cycle interactions provide the foundation for achieving forest-based adaptation and mitigation goals.•Forests can be used, in particular, to mitigate problems related to water scarcity and global warming.•In addition to up- and downstream relationships, policy frameworks need to consider the transboundary nature of up- and downwind forest, water and energy cycle interactions.•Alongside the local level, regional and continental policy-making frameworks are necessary for adequate consideration of transboundary forest, water and energy cycle interactions. Forest-driven water and energy cycles are poorly integrated into regional, national, continental and global decision-making on climate change adaptation, mitigation, land use and water management. This constrains humanity’s ability to protect our planet’s climate and life-sustaining functions. The substantial body of research we review reveals that forest, water and energy interactions provide the foundations for carbon storage, for cooling terrestrial surfaces and for distributing water resources. Forests and trees must be recognized as prime regulators within the water, energy and carbon cycles. If these functions are ignored, planners will be unable to assess, adapt to or mitigate the impacts of changing land cover and climate. Our call to action targets a reversal of paradigms, from a carbon-centric model to one that treats the hydrologic and climate-cooling effects of trees and forests as the first order of priority. For reasons of sustainability, carbon storage must remain a secondary, though valuable, by-product. The effects of tree cover on climate at local, regional and continental scales offer benefits that demand wider recognition. The forest- and tree-centered research insights we review and analyze provide a knowledge-base for improving plans, policies and actions. Our understanding of how trees and forests influence water, energy and carbon cycles has important implications, both for the structure of planning, management and governance institutions, as well as for how trees and forests might be used to improve sustainability, adaptation and mitigation efforts.